2014
DOI: 10.3389/fncel.2014.00211
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic modulation of blood brain barrier: perspectives on Parkinson’s disease

Abstract: The blood–brain barrier (BBB) is a tightly regulated interface in the Central Nervous System (CNS) that regulates the exchange of molecules in and out from the brain thus maintaining the CNS homeostasis. It is mainly composed of endothelial cells (ECs), pericytes and astrocytes that create a neurovascular unit (NVU) with the adjacent neurons. Astrocytes are essential for the formation and maintenance of the BBB by providing secreted factors that lead to the adequate association between the cells of the BBB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
293
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(309 citation statements)
references
References 145 publications
(261 reference statements)
3
293
0
13
Order By: Relevance
“…Second, reactive astrocytes can also promote BBB function during a CNS insult [57,124]. Our group and others have shown that reactive perivascular astrocytes upregulate Shh in MS lesions [92,154].…”
Section: Reactive Astrogliosismentioning
confidence: 86%
See 1 more Smart Citation
“…Second, reactive astrocytes can also promote BBB function during a CNS insult [57,124]. Our group and others have shown that reactive perivascular astrocytes upregulate Shh in MS lesions [92,154].…”
Section: Reactive Astrogliosismentioning
confidence: 86%
“…The physical, molecular, and transporter barrier properties of the BBB are each responsible for maintaining CNS homeostasis [1,45,52]. Histopathological analysis of various neurologic diseases have revealed that BBB dysregulation and breakdown is a common feature in many of these disorders, lending proof to the hypothesis that a functional BBB is required for a healthy CNS [2,6,49,[53][54][55][56][57]. Moreover, there is evidence that this works in the opposite direction as well; that a healthy CNS microenvironment is essential for maintaining the functional barrier properties of the BBB via cross-talk between neural cells and ECs [2].…”
Section: Features Of the Adult Bbbmentioning
confidence: 98%
“…This antioxidant activity of astrocytes helps to protect the neuron against the oxidative stress preventing the damage of DNA, RNA, and proteins [45, 46]. In this regard, previous works indicated that astrocytes are pivotal mediators in TBI due to their ability to provide neurons (and other cells) metabolic support [47-49]. …”
Section: Cellular and Molecular Alterations After Tbimentioning
confidence: 99%
“…Astrocytes are recognized for being multifunctional housekeeping cells involved in a permanent cross-talk with neurons and other neighbouring glial cells [52]. They regulate the concentration of potassium, sodium and glutamate at the synaptic cleft [47-49], provide lactate and glutamine to neurons and participate in neuron signalling modulation [53-57]. …”
Section: Role Of Astrocytes After Tbimentioning
confidence: 99%
“…Junctions are dynamic structures capable to alter the size of intercellular gaps during some minutes by remodeling the cytoskeleton, and the pericapillary reaction of the astrocytes adjoining the capillaries signifies the increase of capillary wall permeability [14,15]. Alterations of the neuron ultrastructure were of the adaptive character in response to the action of the oxidative factor, and were characterized by the increase of block-synthesizing organelle activity.…”
Section: Lsmentioning
confidence: 99%